AGILE SYSTEMS IN HEALTHCARE: Report from the Inaugural Medical Device Agile Systems Development Workshop. Issue 2 (July 2016) - Unger, Chris; Celentano, Mike
ABSTRACT: The INCOSE Healthcare Working Group observed that many of our members from medical device companies use, or partially use, agile methods for software development. The Association for Advancing Medical Instrumentation published a report in 2012, with the US Food and Drug Administration (FDA), on applying agile methods for medical device software. A small group of representatives from various organizations in the Midwest region of the US convened to discuss the application of agile to "systems" development, which was relatively new for all of our attendees. The conference identified practices which were relatively common, and other candidate best practices which were applied by only a few organizations. Barriers to adoption and potential strategies for overcoming those barriers were identified and discussed. The group agreed that a series of continuing conferences on agile approaches to systems engineering in medical device development would be helpful.